1994
DOI: 10.21273/hortsci.29.8.906
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Embryogenesis and Plant Regeneration in Cucumber

Abstract: The embryogenic capacity of seven cucumber (Cucumis sativus L.) cultivars was examined by tissue culture of cotyledon, young first-leaf, and internode explants. Somatic embryogenesis frequencies differed significantly among the tested cultivars, and `Fushinarimidori' produced the highest number of embryos from either cotyledons or young first leaves. Cotyledon- and first-leaf-derived calluses produced more embryos than calluses from internodes. Somatic embryos were induced fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
15
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 22 publications
5
15
0
1
Order By: Relevance
“…AC is used to remove phytohormone auxin from the developing embryo. The addition of AC can enhance the conversion of somatic embryo to plantlets during maturation of somatic embryos [26,27]. It was also reported that AC caused detrimental effect such adsorption of various medium components which are inhibitory to the growth or development [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…AC is used to remove phytohormone auxin from the developing embryo. The addition of AC can enhance the conversion of somatic embryo to plantlets during maturation of somatic embryos [26,27]. It was also reported that AC caused detrimental effect such adsorption of various medium components which are inhibitory to the growth or development [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…It may be achieved by organogenesis and somatic embryogenesis using different explants: cotyledons (Jia et al 1986, Trulson andShahin 1986), seedling leaves (Orezyk and Malepszy 1985, Seo et al 2000 cotyledons and leaves (Punja et al 1990) and hypocotyls (Nishibayashi et al 1996, Raharjo et al 1996. Methods for plant regeneration from cucumber callus via organogenesis (Chee 1990, Punja et al 1990, Nishibayashi et al 1996, Seo et al 2000, suspension culture (Chee andTricoli 1988, Lou andKako 1994) or by somatic embryogenesis on solid medium (Chee 1990) from the callus derived from cotyledon/hypocotyl explants have been also described. However, cucumber regeneration via organogenesis is still limited due to low regeneration frequency and the results found to be genotype dependent (Wehner andLocy 1981, Kim et al 1988).…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…Initial culture on picloram or NAA, or on 2,4-D at a low concentration (1.4 #M) did not result in any embryogenic callus formation. Embryogenic callus formation increased to 40% if during the initial phase of the culture (10 days), the 2,4-D concentration was raised to 14 #M. Prolonged culture on 14 #M 2,4-D resulted in less embryogenic callus formation.Abbreviations: BA -benzylaminopurine; 2,4-D-2,4-dichlorophenoxyacetic acid; NAA -naphthaleneacetic acid Embryogenic callus formation from leaf explants of cucumber has been reported by various authors (Malepszy and Nadolska-Orczyk 1983;Chee and Tricoli, 1988;Bergervoet et al 1989;Debeaujon and Branchard, 1993;Lou and Kako, 1994). In our hands, the published procedures resulted in low frequencies of embryogenic callus formation.…”
mentioning
confidence: 75%
“…Abbreviations: BA -benzylaminopurine; 2,4-D-2,4-dichlorophenoxyacetic acid; NAA -naphthaleneacetic acid Embryogenic callus formation from leaf explants of cucumber has been reported by various authors (Malepszy and Nadolska-Orczyk 1983;Chee and Tricoli, 1988;Bergervoet et al 1989;Debeaujon and Branchard, 1993;Lou and Kako, 1994). In our hands, the published procedures resulted in low frequencies of embryogenic callus formation.…”
mentioning
confidence: 75%